Epidemiology and transmission dynamics of tuberculosis among internal migrants in Hangzhou: A retrospective analysis from 2013 to 2022 - Qingchun Li; Zike Cheng; Qinglin Cheng; Ruoqi Dai; Yifei Wu; Liyun Ai; Yinyan Huang; Qingjun Jia; Nan jiang; Xuexin Bai; Zijian Fang; Xu Song; et al. (Travel Medicine and Infectious Disease)
Background: Tuberculosis (TB) remains a critical public health challenge in China, particularly amid rapid urbanization and internal migration. This retrospective study analyzed the epidemiology and transmission dynamics of TB among internal migrants (IMTB) versus local residents (LRTB) in Hangzhou, China, from 2013 to 2022. Methods: Data from 47,659 pulmonary TB cases were extracted from the national Tuberculosis Information Management System. Results: IMTB accounted for 21.88 % of cases, with patients significantly younger (mean age 33.45 vs. 51.50 years, P < 0.0001) and fewer bacteriologically confirmed diagnoses (34.9 % vs. 41.8 %, P < 0.0001) compared to LRTB. Treatment success rates were higher among IMTB (95.0 % vs. 89.7 %, P < 0.0001). Spatial clustering of IMTB occurred in industrial districts, primarily originating from Anhui, Guizhou, and Jiangxi provinces. Conclusion: Migration-driven TB transmission highlights the need for adaptive control strategies in urbanizing settings.